2020
DOI: 10.1111/jdv.16085
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of digital staining for ex vivo confocal laser scanning microscopy

Abstract: BackgroundEx vivo confocal laser scanning microscopy (CLSM) is a novel diagnostic tool for the fast examination of native tissue. However, CLSM produces black/white/green images, depending on the refraction indices of the tissue structures, complemented by nuclear fluorescence staining, which the vast majority of Mohs surgeons and dermatopathologists are not trained to interpret. Digital staining is applicable to ex vivo CLSM investigations to simulate the images of conventional slides stained with haematoxyli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 11 publications
3
21
0
1
Order By: Relevance
“…In accordance with the first study on DS of healthy skin [24], we could visualize the main anatomical structures, as in H&E slides, with high concordance rates. Fat tissue was visible in every mode as an aggregation of empty, lobulated spaces with bright (blue‐lilac in DS) nuclear elements pushed to the periphery; muscle fibers were displayed as elongated elements with bright (blue‐lilac in DS) nucleus, while connective tissue in scars had a pink appearance in DS.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…In accordance with the first study on DS of healthy skin [24], we could visualize the main anatomical structures, as in H&E slides, with high concordance rates. Fat tissue was visible in every mode as an aggregation of empty, lobulated spaces with bright (blue‐lilac in DS) nuclear elements pushed to the periphery; muscle fibers were displayed as elongated elements with bright (blue‐lilac in DS) nucleus, while connective tissue in scars had a pink appearance in DS.…”
Section: Resultssupporting
confidence: 82%
“…As a consequence, the user can experience a direct and intuitive comparison to the standard H&E features. A pilot study on healthy skin reported a very high correlation between digitally stained FCM mosaics and H&E sections, although no statistical analysis was provided [24]. The authors could correlate the morphology of main skin structures, including appendages, and even noticed a better visualization of adipocytes and hair follicles.…”
Section: Resultsmentioning
confidence: 99%
“…This is achieved via the similarity of tissue reflection with eosin staining and replacement of the nuclear hematoxylin staining by acridine orange fluorescence [27]. Digital HE staining has already been comprehensively evaluated in healthy skin samples [28].…”
Section: Introductionmentioning
confidence: 99%
“…While dermal fibers can be visualized because of their autofluorescence at 488 nm (vs 638 nm) in control unstained tissues, accentuation of dermal fibers (collagen, elastin) in AO images was prominently visible after staining, suggesting some degree of nonspecific staining. Histology correlation studies, as well as prospective clinical investigations to evaluate diagnostic accuracy (sensitivity, specificity, positive and negative predictive value), would be needed to definitively test and prove DRAQ5's enhanced diagnostic value relative to that of AO [24, 25].…”
Section: Discussionmentioning
confidence: 99%